Hydrothermal Carbonization of Sludge – Optimization for Dewaterability - Malhotra Milan; Pawlak-Kruczek Halina; Tran Khanh-Quang (Environmental and Climate Technologies)
Anaerobic sludge digestate (SD), a by-product from anaerobic digestion, can be used as fuel. However, the high moisture content and poor dewatering properties makes SD unfit for direct energy applications such as combustion and thermal gasification. Hydrothermal carbonization (HTC) process, which uses water as a reaction medium, is a suitable pretreatment method to enhance the dewatering and fuel properties of SD. Hydrochar (HC) obtained after HTC of SD can be used to substitute some fraction of coal for various energy applications. In the present study, HTC of SD was optimized, with respect to dewaterability of HC, using the design of experiment (DoE) approach and the reaction conditions were varied from 158−242 °C and ~10−138 min, respectively. Dewatering assessment of the treated slurry showed that a minimum reaction temperature of 190 °C for 34 min was required to substantially improve digestate’s dewaterability.